Bi-level Optimization Strategy for Energy Storage Siting and Sizing Supporting Offshore Wind Farm Primary Frequency Regulation and Black Start - Li, Feng; Chen, Danqing; Luo, Shuxin; Chen, Honglin; Zhao, Jianyong; Nian, Heng (2025 4th International Conference on Power System and Energy Technology (ICPSET), 2025)
To meet the demands for primary frequency regulation and black start capabilities during system frequency regulation and fault recovery in offshore wind power, the integration of fast-response energy storage systems has become a critical measure. This paper proposes a bi-level optimization configuration model for the optimal siting and sizing of energy storage within offshore wind farms. The upper level utilizes a Particle Swarm Optimization (PSO) algorithm to optimize the energy storage capacity, power, and wind power reserve capacity coefficient. This optimization is driven by multiple objectives, including frequency regulation performance, black start sequence, wind energy utilization, and annualized cost. Conversely, the lower level employs a Genetic Algorithm (GA) to optimize the energy storage location within the distribution network, subject to capacity parameter constraints, with the aim of minimizing voltage deviation and active power loss. Through the coupled operation of the upper and lower levels, the optimal energy storage capacity, installation location, and wind power reserve capacity are collectively determined. Finally, a case study conducted on the IEEE 33-node system validates the efficacy of the proposed method in enhancing system stability, improving frequency regulation performance, and achieving economic efficiency in configuration.